Autoimmune cerebellopyramidal syndrome as a complex form of autoimmune cerebellar ataxia: a cohort study - Liu, Mange; Ren, Haitao; Fan, Siyuan; Zhang, Le; Guan, Hongzhi (Frontiers in Immunology, 2025)
BackgroundAutoimmune cerebellar ataxia (ACA) is a significant and treatable cause of sporadic cerebellar syndrome. Pyramidal tract damage affects approximately 30% of ACA patients, profoundly impacts motor function and prognosis, yet this complex form remains under-investigated.MethodsWe retrospectively analyzed patients with pyramidal signs from our institutional ACA cohort, excluding those with intrinsic upper motor neuron impairment due to specific ACA subtypes. Clinical and paraclinical data were compared between patients with and without pyramidal signs.ResultsAmong the 48 ACA patients with pyramidal signs, primary autoimmune cerebellar ataxia was the most common subtype (50%), and neuronal antibodies were detected in 66.7%. Compared to ACA patients without pyramidal signs, those with pyramidal signs were younger at onset (44 vs 47 years, p=0.048) and more frequently presented with limb ataxia (97.9% vs 78.8%, p=0.002) and diplopia (48.9% vs 18.2%, p<0.001). Brain MRI revealed pyramidal tract and/or semiovale centrum lesions in 29.8% of patients with pyramidal signs, a finding absent in the non-pyramidal sign group (p<0.001), which could subside with immunotherapy. Cerebrospinal fluid (CSF) analysis showed higher protein concentration and a significantly higher rate of specific oligoclonal bands in the pyramidal sign group. Patients with pyramidal signs had a significantly higher risk of relapse (52.5% vs 32.8%, p=0.034).ConclusionsAutoimmune cerebellopyramidal syndrome represents a distinct and complex ACA phenotype, characterized by unique clinical and imaging features, CSF abnormalities indicative of a more pronounced autoimmune response, and a higher relapse rate. Comprehensive evaluation and long-term maintenance immunotherapy may be warranted in these patients.